Fenomena Aliran Sempalan dalam Islam: Dinamika Sosiologis Eksistensi Ahmadiyah Qadian di Indonesia - Kurniati Kurniati; Misbahuddin Misbahuddin; Abdurrahman Abubakar Bahmid (Al-Mizan (e-Journal), 2023)
This research aims to understand the sociological phenomenon of splinter sects in Islam with the dynamics of the existence of the Qadian Ahmadiyah in Indonesia as the object of study. The growth of Islamic sects is part of social interaction and religious teachings that become a treasure of Islamic theological thought, such as Ahmadiyah. As a religious organization, the existence of Ahmadiyah, especially the Qadian sect, raises interesting sociological phenomena to be studied. Considering that each sect has a different social character at the beginning of its birth, so did the Ahmadiyah. sociologically Ahmadiyya is a portrait of the struggle of Islam in India with the theological character that surrounds it. This study is library research that aims to analyze the history of Islamic theological thought using a social approach. The existence of Ahmadiyah continues to generate pros and cons among Indonesian Muslims. The issuance of MUI Fatwa and SKB of 3 Ministers became the legitimization of Ahmadiyah's policy to be heretical and prohibited in Indonesia. The social impact is that the prohibition and misdirection of Ahmadiyah congregations have created a bad stigma in society. Until now, Ahmadiyah congregations and other Muslim communities still have unfavorable relations, often leading to conflict. However, not all regions in Indonesia are negative. Some areas have a positive environment towards the Ahmadiyah Congregation.